2013
DOI: 10.1021/jf401627m
|View full text |Cite
|
Sign up to set email alerts
|

Stable Binding of Alternative Protein-Enriched Food Matrices with Concentrated Cranberry Bioflavonoids for Functional Food Applications

Abstract: Defatted soy flour (DSF), soy protein isolate (SPI), hemp protein isolate (HPI), medium roast peanut flour (MPF) and pea protein isolate (PPI) stably bind and concentrate cranberry (CB) polyphenols, creating protein/polyphenol-enriched matrices. Proanthocyanidins (PAC) in the enriched matrices ranged from 20.75 mg/g (CB-HPI) to 10.68 mg/g (CB-SPI). Anthocyanins (ANC) ranged from 3.19 mg/g (CB-DSF) to 1.68 mg/g (CB-SPI), while total phenolics (TP) ranged from 37.61 mg/g (CB-HPI) to 21.29 mg/g (CB-SPI). LC-MS in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
59
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 30 publications
6
59
0
Order By: Relevance
“…The experiments demonstrated that binding process does not alter the anti-inflammatory activity of phytochemicals, but stabilized them in a dry concentrated form. These results support our previous findings indicating that the binding process does not affect the biological activity of phytochemicals [16].…”
Section: Bioactivity Of Phytoactives Bound To Matricessupporting
confidence: 93%
See 2 more Smart Citations
“…The experiments demonstrated that binding process does not alter the anti-inflammatory activity of phytochemicals, but stabilized them in a dry concentrated form. These results support our previous findings indicating that the binding process does not affect the biological activity of phytochemicals [16].…”
Section: Bioactivity Of Phytoactives Bound To Matricessupporting
confidence: 93%
“…Fortification of the SPI matrices with muscadine or kale bioactives did not raise the estimated calories/100 g dry matrix (366 and 376 cal/ 100 g for muscadine and kale, respectively compared to The changes in proximate analysis for some muscadine fortified ingredients can be attributed to solubility of some of the protein isolates in the discarded supernatant after centrifugation with the juice [16]. Protein decrease in the kale fortified proteins is due to the increase in weight (due to addition of the vegetable compounds) of the final product by the co-drying technique which led to dilution of proteins per 100 g dry wt.…”
Section: Nutritional Analysis Of Matricesmentioning
confidence: 90%
See 1 more Smart Citation
“…2 There is a growing interest on the possibility of polyphenols application (including RA) in functional foods, nutraceutical, and pharmaceutical industries. [2][3][4][5] However, the effectiveness of polyphenols depends on preserving the stability and bioavailability of the active ingredients.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported on a straightforward food grade technology for biofortification of edible proteins with fruit phytoactives [11,12]. Both bioavailability and healthprotective efficacy of the phytoactive constituents were enhanced by the co-delivery with edible proteins in a complexed aggregate matrix [13].…”
mentioning
confidence: 99%